2023
DOI: 10.1093/nsr/nwad061
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional (n = 1) ferroelectric film solar cells

Abstract: Molecular ferroelectrics with excellent ferroelectric properties and a low processing temperature, a narrow bandgap, and light weightiness have shown great potential in the photovoltaic field. However, two-dimensional (2D) perovskite solar cells with high tunability, excellent photo-physical properties, and superior long-term stability are limited by the poor out-of-plane conductivity from intrinsic multi-quantum well electronic structures. This work uses 2D molecular ferroelectric as the absorbing layer to br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…As shown in Figure e, after polarization with an applied voltage of 0.6 V, the V OC of the device prepared with a precursor solution of 0.2 mol/L increased to 1.198 V, and the J SC increased to 1.055 mA/cm 2 , indicating that the device can achieve multiple adjustments of photovoltaic performance after polarization with different applied electric fields. This is consistent with previous reports on ferroelectric (4,4-difluoropiperidinium) 2 PbI 4 . In Figure , the hysteresis of the photovoltaic performance of the device increases with the increase in film thickness.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…As shown in Figure e, after polarization with an applied voltage of 0.6 V, the V OC of the device prepared with a precursor solution of 0.2 mol/L increased to 1.198 V, and the J SC increased to 1.055 mA/cm 2 , indicating that the device can achieve multiple adjustments of photovoltaic performance after polarization with different applied electric fields. This is consistent with previous reports on ferroelectric (4,4-difluoropiperidinium) 2 PbI 4 . In Figure , the hysteresis of the photovoltaic performance of the device increases with the increase in film thickness.…”
Section: Resultssupporting
confidence: 92%
“…This is consistent with previous reports on ferroelectric (4,4-difluoropiperidinium) 2 PbI 4 . 46 In Figure 4, the hysteresis of the photovoltaic performance of the device increases with the increase in film thickness. If the hysteresis is related to the ferroelectric properties of the film, the change in photovoltaic performance of the polarized film should be consistent with the amplitude of the hysteresis change.…”
Section: ■ Experimental Detailsmentioning
confidence: 98%
“…(D) The J – V curves based on 2D (DFPD) 2 PbI 4 ferroelectric PSCs before and after positive poling. Reproduced under terms of the CC‐BY license 69 . Copyright 2023, Oxford University Press.…”
Section: Perovskite Solar Cells With Ferroelectricitymentioning
confidence: 99%
“…Zou et al developed a 2D perovskite solar cell that employs a two-dimensional molecular ferroelectrics (4,4-difluoropiperidinium) 2 PbI 4 as an absorption layer, breaking through the limitations of multiple quantum wells by out-plane ferroelectric polarization (Figures 8A,B). 69 After positive poling, the surface potential of the ferroelectric layer decreased by about −311 mV (non-ferroelectric (PEA) 2 PbI 4 has little changes) with a 1 V bias voltage for 300 s (Figure 8C), leading to improved photoelectric performance of ferroelectric PSCs. This change is mainly attributed to the charge accumulation/photo-generated charge transport on the surface under the depolarization field promotion.…”
mentioning
confidence: 99%
“…111 Researchers have found that molecular ferroelectrics (MFs) display high ferroelectricity and a field amplification effect, indicating their potential in neuromorphic devices. 112,113 Cai et al introduced a 2T ferroelectric synaptic device utilizing a MF/semiconductor interface, as illustrated in Fig. 4(e).…”
Section: Neurosynaptic Devices Based On Two-terminal Memristorsmentioning
confidence: 99%